2022
DOI: 10.3389/fcvm.2022.923066
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated autophagy-related genes in septic cardiomyopathy: Comprehensive bioinformatics analysis based on the human transcriptomes and experimental validation

Abstract: Septic cardiomyopathy (SCM) is severe organ dysfunction caused by sepsis that is associated with poor prognosis, and its pathobiological mechanisms remain unclear. Autophagy is a biological process that has recently been focused on SCM, yet the current understanding of the role of dysregulated autophagy in the pathogenesis of SCM remains limited and uncertain. Exploring the molecular mechanisms of disease based on the transcriptomes of human pathological samples may bring the closest insights. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…As described in our previous study, 29 the microarray datasets GSE79962 and GSE54514 were retrieved from the GEO database (https://www.ncbi.nlm.nih.gov/geo/). The transcriptomic data of 11 control hearts (sourced from non-failed donors) and 20 septic hearts (sourced from patients who died from sepsis) were obtained from the GSE79962 dataset, while the transcriptomic data of whole blood samples (within 24 hours of admission to the intensive care unit) from 26 sepsis survivors and 9 sepsis nonsurvivors were obtained from the GSE54514 dataset.…”
Section: Data Collectionmentioning
confidence: 99%
See 4 more Smart Citations
“…As described in our previous study, 29 the microarray datasets GSE79962 and GSE54514 were retrieved from the GEO database (https://www.ncbi.nlm.nih.gov/geo/). The transcriptomic data of 11 control hearts (sourced from non-failed donors) and 20 septic hearts (sourced from patients who died from sepsis) were obtained from the GSE79962 dataset, while the transcriptomic data of whole blood samples (within 24 hours of admission to the intensive care unit) from 26 sepsis survivors and 9 sepsis nonsurvivors were obtained from the GSE54514 dataset.…”
Section: Data Collectionmentioning
confidence: 99%
“…As described in our previous study, 29 the identified DEFRGs were subjected to GO and KEGG enrichment analyses using the clusterProfiler package in the R software. 34 FDR < 0.05 was the criterion for significantly enriched by DEFRGs.…”
Section: Gene Ontology (Go) and Kyoto Encyclopedia Of Genes And Genom...mentioning
confidence: 99%
See 3 more Smart Citations